Pemasaran Udang Vaname di Tengah Hantaman Covid-19 di Desa Mootinelo Kabupaten Gorontalo Utara - Nusi, Arfan; Musran, Melani; Dian, Wahyu (LP2M IAIN Sultan Amai Gorontalo, 2021)
This study discusses the marketing of vaname shrimp in the midst of the Covid-19 hit in Mootinelo village, North Gorontalo. The purpose of this study was to examine the factors and implications of the covid-19 pandemic in the marketing of vaname shrimp. This research uses descriptive methods, collecting observation data, interviews, and documentation. The results of this study indicate that: overall farmers in Mootinelo are 113 hectares, but farmers earn below-average income from sales due to limited shrimp marketing due to Large-Scale Social Restrictions (PSBB) due to the covid-19 pandemic, so that it has an impact on income from the farmers. In addition to covid-19, another problem is that shrimp are susceptible to disease and this has an impact on crop failure and low shrimp production, thus affecting their economic fulfillment.